Informing hydrogeological models with remotely sensed evapotranspiration - Gelsinari, Simone; Doody, Tanya M.; Thompson, Sally E.; Doble, Rebecca; Daly, Edoardo; Pauwels, Valentijn R. N. (Frontiers in Water, 2022)
Remotely sensed evapotranspiration (ET) rates can provide an additional constraint on the calibration of groundwater models beyond typically-used water table (WT) level observations. The value of this constraint, measured in terms of reductions in model error, however, is expected to vary with the method by which it is imposed and by how closely the ET flux is dependant to groundwater levels. To investigate this variability, four silvicultural sites with different access to groundwater were modeled under three different model-data configurations. A benchmark model that used only WT levels for calibration was compared to two alternatives: one in which satellite remotely sensed ET rates from MODIS-CMRSET were also included in model calibration, and one in which the satellite ET data were assimilated, through the Ensemble Kalman Filter, into the model. Large error reductions in ET flux outputs were achieved when CMRSET data were used to calibrate the model. Assimilation of CMRSET data further improved the model performance statistics where the WT was < 6.5 m deep. It is advantageous to use spatially distributed actual ET data to calibrate groundwater models where it is available. In situations where vegetation has direct access to groundwater, assimilation of ET observations is likely to improve model performance.